Unlocking the Potential of Ampenan Old City: A Comprehensive Study of Pentahelix Players' Role in Sustainable Tourism Development in Mataram - Vania Fitri Sedyo Husodo; Fathurrahim; Rizal Kurniansah; Mahsun; Uwi Martayadi (Advances in Tourism Studies, 2023)
This study examines the role of Pentahelix players in developing tourism in the Old City of Ampenan, Mataram City, Indonesia. Despite being designated as one of the Indonesian Heritage Cities Network's 43 cities, Ampenan's tourism potential has not been fully realized, and is even on the decline due to a lack of joint efforts by tourism stakeholders. The Pentahelix players are composed of the government, academia, industry, community, and tourists, and their roles in tourism development are investigated. The study proposes strategies for sustainable tourism development, and data is collected through non-participant observation, unstructured interviews, and documentation. The results highlight the potential of Ampenan Old City as a tourist destination and the contributions of various stakeholders to its development. The study concludes that the Ampenan Old City is a must-visit destination, featuring impressive cultural landmarks, natural beauty, and accessibility, and recommends further collaboration between stakeholders to improve its sustainable development